2003
DOI: 10.1590/s0004-282x2003000300005
|View full text |Cite
|
Sign up to set email alerts
|

The expression of NGFr and PGP 9.5 in leprosy reactional cutaneous lesions: an assessment of the nerve fiber status using immunostaining

Abstract: -The effects of reactional episodes on the cutaneous nerve fibers of leprosy patients was assessed in six patients (three with reversal reactions and three with erythema nodosum leprosum). Cryosections of cutaneous biopsy of reactional lesions taken during the episode and of another sample during the remission period were immunostained with anti-NGFr and anti-PGP 9.5 (indirect immunofluorescence). We found no significant statistical difference in the number of NGFr-and PGP 9.5-positive fibers between the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(18 reference statements)
0
16
0
1
Order By: Relevance
“…Antunes et al (28) also raised this last hypothesis when they found no significant quantitative difference between the number of fibers in biopsies taken during or after reactional episodes. It is worth noting that the lack of immunoreactivity of a neural marker in the endoneurium does not necessarily mean the absence of fibers.…”
Section: Discussionmentioning
confidence: 93%
“…Antunes et al (28) also raised this last hypothesis when they found no significant quantitative difference between the number of fibers in biopsies taken during or after reactional episodes. It is worth noting that the lack of immunoreactivity of a neural marker in the endoneurium does not necessarily mean the absence of fibers.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, we used p75 predominantly as a neuronal marker. A previous study using simultaneous costaining of p75 with axonal marker protein gene product (PGP) 9.5 showed no significant difference in nerve fiber density between both staining in humans, 19 suggesting that p75 is a reasonable pan‐neuronal marker. A distinct advantage of p75 over PGP 9.5 is higher contrast of stained fibers 19 .…”
Section: Discussionmentioning
confidence: 97%
“…A previous study using simultaneous costaining of p75 with axonal marker protein gene product (PGP) 9.5 showed no significant difference in nerve fiber density between both staining in humans, 19 suggesting that p75 is a reasonable pan‐neuronal marker. A distinct advantage of p75 over PGP 9.5 is higher contrast of stained fibers 19 . However, because p75 stains predominantly Schwann cells, the loss of p75 IR is because of either axonal neuropathy with the secondary Schwann cell degeneration or primary degeneration of Schwann cells.…”
Section: Discussionmentioning
confidence: 97%
“…However, such studies have used non-systematic semi-quantitative methods to evaluate the nerve density and the thermal thresholds, and did not exclude treated patients [20], [21], [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%